Influence of Modifying Mixtures on Si Crystal Formation in Al-7%Si Alloy; Metals; Vol. 8, iss. 2 - Zykova A. P. Anna Petrovna; Kazantseva L. A. Lyudmila Alekseevna; Popova N. A. Nataljya Anatoljevna; Vorozhtsov A. B. Aleksandr Borisovich; Kurzina I. A. Irina Aleksandrovna (2018, 2018)
Title screen